Influência dos fatores contingenciais na implementação dos sistemas de controle interno de municípios paranaenses - Ruschel, Ricardo (2023)
Internal Control is an important activity within the Public Administration, as it helps to prevent errors or fraud, subsidizing the manager efficiently and effectively with regard to Public Sector controls. The implementation of Internal Control in public entities has a legal provision based on current legislation, while inspection takes place through the Courts of Accounts. The understanding regarding the implementation of Internal Control can be done, among others, from the Theory of Contingency. In view of this, the research aims to analyze the influence of contingency factors in the implementation of the Internal Control System (SIC), according to the vision of the internal controllers of the municipalities of Paraná. The study was carried out through a quantitative and qualitative research for the problem, regarding the objectives, it was descriptive, and regarding the procedures, it was through a survey and by field research and Structural Equation Modeling by partial least squares. This research, in addition to being original, advances in the production of new knowledge, since in addition to testing the relationship between the contingency variables environment, structure, strategy, technology and size, it is also dedicated to deepening the analysis of such relationships, based on a field research, in which it is necessary to understand in depth the elements that most contribute to these interactions in the same way. A sample of 104 respondents was obtained, who are part of the quantitative survey. As for the qualitative analysis, 8 semi-structured interviews and document analysis were carried out, with city halls from 5 to 430 thousand inhabitants in the State of Paraná. As main results presented, the proposed hypotheses were all rejected. In the quantitative analysis, the evidence found reveals that the Strategy variable had a positive and significant influence, the other variables Environment, Structure, Technology and size did not show the same relationship. On the other hand, in the qualitative analysis it was possible to find evidence that the Environment through the Court of Auditors, Public Ministry, current legislation, political factors and the current economic scenario, the Structure factor with the hiring of new servants, improvement in the administrative structure, continuous training and qualification of professionals, lack of standardization regarding norms, and the Technology factor, the use of systems (software), systems made available by the control bodies, are considered drivers and positively influence the implementation of the ICS. As for the Strategy and Size factors, in the perception of the interviewees, there is no relation with the implementation of the SCI. The research presents a theoretical contribution, by adding new understandings of the Theory of Contingency related to the Public Sector, assisting in decision making and complying with obligations, improving management processes related to the Public Sector, and mainly demonstrating that society may be demanding greater controls for As part of the Public Administration, the lack of demand from external bodies can also be considered, and a more efficient and effective standardization of activities to be developed would contribute to a better implementation of the SCI in city halls